Role of physical activity and sleep duration in growth and body composition of preschool‐aged children. Issue 6 (18th April 2016) - Butte, Nancy F.; Puyau, Maurice R.; Wilson, Theresa A.; Liu, Yan; Wong, William W.; Adolph, Anne L.; Zakeri, Issa F.
Abstract : Objective: The impact of physical activity patterns and sleep duration on growth and body composition of preschool‐aged children remains unresolved. Aims were (1) to delineate cross‐sectional associations among physical activity components, sleep, total energy expenditure (TEE), and body size and composition; and (2) to determine whether physical activity components, sleep, and TEE predict 1‐year changes in body size and composition in healthy preschool‐aged children. Methods: Anthropometry, body composition, accelerometry, and TEE by doubly labeled water were measured at baseline; anthropometry and body composition were repeated 1 year later ( n  = 111). Results: Cross‐sectionally, positive associations between sedentary activity and weight and fat‐free mass (FFM) ( P = 0.009‐0.047), and a negative association between moderate‐vigorous physical activity (MVPA) and percent fat mass (FM) ( P = 0.015) were observed. TEE and activity energy expenditure (AEE) were positively associated with weight, body mass index (BMI), FFM, and FM ( P = 0.0001‐0.046). Prospectively, TEE, AEE, physical activity level, and MVPA, but not sedentary activity, were positively associated with changes in BMI ( P = 0.0001‐0.051) and FFM ( P = 0.0001‐0.037), but not percent FM. Sleep duration inversely predicted changes in FM ( P = 0.005) and percent FM ( P = 0.006). Conclusions: Prospectively, MVPA, TEE, AEE, and physical activity level promote normal growth and accretion of FFM, whereas sleep duration inversely predicts changes in adiposity in preschool‐aged children.